Detection on common deletional alpha-thallasaemia in pregnant lady by polymerase chain reaction - Rosline, Hassan (Pusat Pengajian Sains Perubatan, 2012)
In order to screen the carrier state of the common deletional types of alpha tha/assaemia, we have evaluated a screening protocol and examined the prevalence and the molecular basis of the alpha thalassemia in pregnant women at Hospital Universiti Sains Malaysia (HUSM). Blood samples from two hundred (200) pregnant women were screened for a-thalassaemia. Of these, 16 were later excluded because they had been diagnosed as having HbE trait or the {3-thalassemia trait. Results were evaluated with the standard haemato/ogical analyses including erythrocyte count, haemoglobin quantitation and polymerase chain reaction (PCR) analysis of a-globin gene. Altogether 17 of 184 subjects was detected as a-thalassemia (-a3·7faa and __ sEA; aa genotype) carrier. Analysis of hematologic data showed significantly difference in MCVs and MCH (p=O. 000), and the best cut-off point for predicting the presence of the athalassemia carrier in pregnant women was 86.3fL giving 77% sensitivity and 71% of specificity. -a37 kb single gene deletion (8. 1%) was the commonest a-thalassemia found in this study population followed by double gene South East Asia (-sEA) deletion (1.1%). Thus earlier screening is recommended to be performed to pregnant women and followed by paternal testing as those with -sEA deletion; carry higher risk of having hydrop feta/is baby if the father is also -sEA type carrier.